Effect of standardized hands-on-training in caregivers of children with tracheostomy - Yılmaz Yeğit, Cansu; Ayzıt Kılınç, Ayşe; Guliyeva, Aynur; Atağ, Emine; Yazan, Hakan; Can Oksay, Sinem; Köstereli, Ebru; Uzuner, Selçuk; Onay, Zeynep Reyhan; Hepkaya, Evrim; Ergenekon, Almala Pınar; Kalyoncu, Mine; et al. (European Respiratory Society Journals Ltd, 2021)
Introduction: The pediatric tracheostomy related mortality mostly occurs due to accidental decannulation and cannula obstruction. The caregivers may be discharged with inadequate knowledge. Aims and objectives: Simulation training can highlight skills regarding tracheostomy care. Our aim is to investigate if a standardized hands-on-training improves knowledge and skills among caregivers. Methods: Before the traning, we applied a pretest to caregivers in order to assess their knowledge and current practises. Skills were evaluated by two simulation scenarios in a patient model: cannula change and aspiration. After one hour theoretical and practical hands-on training, the same post-test was applied, skills were reevaluated regarding cannula change and aspiration with practical tests. Results: The multicenter study included 65 caregivers of patients with tracheostomy. The median score of the theoretical test including 23 questions improved from 12 to 18 (p<0.001). The specific knowledge questions that were considered critical for tracheostomy care including minimum number of aspiration per day, required frequency of tracheostomy cannula change, solutions recommended for tracheostomy skin care, the pressure for the aspiration, mean duration of aspiration and the depth of aspiration also improved significantly after the education (p<0.001 for all of the specific questions). There was a significant improvement in both cannula change and aspiration skills regarding median scores of correct steps in procedures (p<0.001). Conclusions: A standardized hands-on training is highly effective to increase the rate of proper practices for tracheostomy care and should be implemented for all centers.
Keywords: Tracheostomy; Caregivers; Standardized Hands-On-Training